Optimization of Casting in Early-onset Scoliosis. Issue 4 (April 2019) - Fedorak, Graham T.; Stasikelis, Peter J.; Carpenter, Ashley M.; Nielson, Alexandra N.; D'Astous, Jacques L.
Abstract : Background: Early-onset scoliosis is a spine deformity that presents before the age of 3 years. When compared with age-matched controls, children with the condition are known to be at risk for significant morbidity and mortality. Although many works support the use of casting for this condition, the key technical factors to optimize the outcomes of casting are not clear. This work was designed to evaluate the role of frequency of radiographic imaging and over the shoulder straps in the outcomes of casting. Methods: Two surgeons at 2 centers followed nearly identical protocols for applying casts for early-onset scoliosis. At center A, the surgeon hoped to improve outcomes by obtaining radiographs after each cast and by reinforcing the cast with shoulder straps. At center B, the surgeon did not use shoulder straps and limited radiographs to once every 6 months. Children were included if they were 3 years or below of age and had a curve of ≥50 degrees at the time of the first cast and had a minimum of 3 years of follow-up. Center was used as a variable in a multivariable regression that also included: age at first cast, initial curve magnitude, and presence of a syrinx or genetic syndrome with the outcome of curve resolution. Results: There were 40 children at center A, 9 of whom experienced resolution of their scoliosis. There were 36 children at center B, and 11 demonstrated scoliosis resolution. At center A, 2 of 10 children with a syrinx or genetic syndrome demonstrated curve resolution while 7 of 30 without these comorbidities did. At center B 3 of 10 children with a syrinx or genetic syndrome had curve resolution while 8 of 26 children without these comorbidities did. Conclusions: The children in group A demonstrated results very similar to the children of group B. Thus, the extra burden of shoulder straps and frequent radiographs are unnecessary. Level of Evidence: Level III.